ELECTRIC DOUBLE LAYER CAPACITOR AND MANUFACTURING METHOD THEREOF, POWER-STORAGE MODULE, AND POWER STORAGE DEVICE - ISEYA YUKI (2016)
PROBLEM TO BE SOLVED: To provide: an electric double layer capacitor which is adaptive to various types and inexpensive and enables mass production; a method for manufacturing such an electric double layer capacitor; a power-storage module arranged by use of such an electric double layer capacitor; and a power storage device.SOLUTION: An electric double layer capacitor comprises: an elongated internal conductor 10 serving as a current collecting electrode; a first polarizable electrode 20 wound around the internal conductor 10 with a predetermined winding angle ; a separator 30 wound around the first polarizable electrode 20 with the predetermined winding angle ; a second polarizable electrode 40 wound around the separator 30 with the predetermined winding angle ; an external conductor 50 which is a current collecting electrode provided on the external surface of the second polarizable electrode 40; and an electrolytic solution 60 impregnated into between the internal conductor 10 and the first polarizable electrode 20, between the first polarizable electrode 20 and the separator 30, and between the separator 30 and the external conductor 50. The predetermined winding angle of the first polarizable electrode 20, the separator 30, and the second polarizable electrode 40 is set to be less than 90° to a lengthwise direction of the internal conductor 10.SELECTED DRAWING: Figure 1 【課題】さまざまな品種に対応でき、安価で大量生産可能な電気二重層キャパシタとその製造方法を提供し、また、この電気二重層キャパシタを用いた蓄電モジュール、及び蓄電装置を提供する。【解決手段】集電極である長尺状の内部導体１０と、内部導体１０上に所定の巻回角θで巻回された第１分極性電極２０と、第１分極性電極２０上に所定の巻回角θで巻回されたセパレータ３０と、セパレータ３０上に所定の巻回角θで巻回された第２分極性電極４０と、第２分極性電極４０の外面に設けられた集電極である外部導体５０と、内部導体１０と第１分極性電極２０、第１分極性電極２０とセパレータ３０、及びセパレータ３０と外部導体５０とのそれぞれの間に含浸された電解液６０と、を有し、第１分極性電極２０、セパレータ３０、及び第２分極性電極４０の所定の巻回角θを、内部導体１０の長尺方向に対して９０?未満に設定して電気二重層キャパシタを構成する。【選択図】図１